2011
DOI: 10.1007/s00192-011-1554-5
|View full text |Cite
|
Sign up to set email alerts
|

Anterior sacrospinous ligament fixation associated with paravaginal repair using the Pinnacle™ device: an anatomical study

Abstract: Anterior SSL fixation associated with paravaginal repair using the Pinnacle™ device was not reproducible every time in this cadaver study. These results confirm the need for specific training before starting anterior SSL fixations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 16 publications
0
5
0
1
Order By: Relevance
“…Cayrac reported that 50% of Pinnacle tips were properly placed in the sacrospinous ligament in a cadaveric study. 12 If our study found a similar outcome, we could estimate a 50% incorrect placement rate with a 95% CI of 28-72%. The 6-month follow-up period was chosen because it was felt that any migration of the tip would most likely occur within the first months after surgery, before complete wound healing.…”
Section: Methodsmentioning
confidence: 62%
See 1 more Smart Citation
“…Cayrac reported that 50% of Pinnacle tips were properly placed in the sacrospinous ligament in a cadaveric study. 12 If our study found a similar outcome, we could estimate a 50% incorrect placement rate with a 95% CI of 28-72%. The 6-month follow-up period was chosen because it was felt that any migration of the tip would most likely occur within the first months after surgery, before complete wound healing.…”
Section: Methodsmentioning
confidence: 62%
“…PFDI-20 scores improved for all ten women. Median PISQ-12 scores improved for the four women who were sexually active (26 versus 13; IQR 23-41 versus IQR [12][13][14], although tests of statistical significance were not performed because of the small sample size. …”
Section: Resultsmentioning
confidence: 99%
“…In most of the publications, it is recommended in sacrospinous -sacrotuberous fixation to place the sutures at a distance at least 20 mm medial to the ischial spine and put the suture near to the lower than the upper border of the SSL to avoid injury of the pudendal nerve. 10 In a cadaveric study, Manning and Arnold concluded that the vascular and nerve anatomy behind and in the vicinity of the sacrospinous ligament is enormously variable and that suture placement two fingerbreadths medial to the spine does not guarantee safety. 11 In this modified technique, we are essentially making use of the sacrospinous/sacrotuberous complex.…”
Section: Discussionmentioning
confidence: 99%
“…Kasyanet al described ureteral injury which was diagnosed after surgery but revealed urine leakage extending to the inter-fascial space of the right hip suggesting intra operative direct injury to the ureter secondary to dissection and not kinking [10]. Cayrac et al in his cadaver study confirmed that the ureter can be twisted because of the mesh traction [11]. Doucede et al describe ureteral injury after placement of Uphold ™ mesh [5].…”
Section: Discussionmentioning
confidence: 99%